Bidirectional ventricular tachycardia induced by respiratory alkalosis mediated hypokalemia in a patient with acute ischemic heart failure. Issue 12 (22nd August 2021) - Kulahcioglu, Seyhmus; Baysal, Pınar Karaca; Kup, Ayhan; Imanov, Elmin; Uslu, Abdulkadir; Demir, Serdar; Gulsen, Kamil
Abstract: Bidirectional ventricular tachycardia (BVT) is a rare arrhythmia that is generally observed in patients with catecholaminergic ventricular tachycardia or digoxin overdose. Herein, we present a case of BVT and electrical storm (ES) in an acute ischemic heart failure patient that is typically induced by hypokalemia. The patient was in invasive mechanical ventilator (MV) support and hypokalemia was related to acute respiratory alkalosis and that caused refractory hypokalemia despite intravenous (IV) potassium replacement. We also discuss our approach to solve refractory hypokalemia caused by respiratory alkalosis.